2013
DOI: 10.1111/nep.12084
|View full text |Cite
|
Sign up to set email alerts
|

Research issues in Elderly patients: gaps in knowledge and suggested directions.

Abstract: Concentration of research is recommended in the following areas: Prospective studies of the appropriateness, relevance, timing and sustainability of dialysis in elderly patients Health related quality of life (HRQoL) in older patients choosing not to dialyse and in those choosing to dialyse with comparison to a matched population without renal disease Methods of communication of prognosis and factors affecting decision making Models of care - comparative studies to delineate how best to deliver renal supportiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…repeated needle sticks, fistula placement and maintenance, lifelong need) and prognosis. This is consistent with research showing that patients often are unprepared for dialysis [19,42,43] and may experience regret [13,44]. Many patients directly requested prognostic information and suggested that future patients be advised of prognosis.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…repeated needle sticks, fistula placement and maintenance, lifelong need) and prognosis. This is consistent with research showing that patients often are unprepared for dialysis [19,42,43] and may experience regret [13,44]. Many patients directly requested prognostic information and suggested that future patients be advised of prognosis.…”
Section: Discussionsupporting
confidence: 81%
“…Many patients directly requested prognostic information and suggested that future patients be advised of prognosis. Consistent with the SDM literature [45][46][47][48], patients preferred deliberative conversations with clinicians, although mostly described prescriptive interactions.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation